Quail Breeder Typology and Analysis of Business Performance Differences in Sleman Regency - Marosimy Millaty; Budi Sutiono Pratama Nugraha; Meita Puspa Dewi; Marlianasari Putri (Politeknik Siber Cerdika Internasional, 2026)
Background: Quail farming in Indonesia faces substantial business risks due to feed-price volatility, with feed accounting for approximately 69% of total production costs, and unstable farm-gate egg prices. Despite operating with similar production inputs, farmers demonstrate considerable variation in productivity and technical efficiency. However, cluster-based studies examining the typology of quail farmers remain limited in the Indonesian agribusiness literature. Objective: This study aimed to identify the typology of quail farmers and examine differences in business performance among farmer groups in Sleman Regency, Special Region of Yogyakarta. Methods: This study employed a quantitative approach using survey data collected from 30 laying-quail farmers selected through purposive sampling. K-means cluster analysis was used to classify the farmers according to age, farming experience, and marketing adaptation strategies. Furthermore, a one-way analysis of variance (ANOVA) was conducted to examine differences in egg productivity and technical efficiency among the identified clusters. Results: The farmers were classified into three typologies: traditional, semi-adaptive, and adaptive. Traditional farmers tended to be older, had more farming experience, and relied on conventional marketing channels involving intermediaries. In contrast, adaptive farmers were generally younger and employed direct-to-consumer marketing strategies. Despite these typological differences, the ANOVA results revealed no statistically significant differences in egg productivity (p = 0.565) or technical efficiency (p = 0.486). These findings suggest that adaptive behavior has not yet resulted in measurable performance advantages. Conclusion: This study contributes to a better understanding of farmer heterogeneity in the quail-farming sector and provides evidence-based policy implications for designing targeted agricultural extension programs tailored to each farmer typology. These programs should focus specifically on strengthening the digital marketing capabilities of traditional farmers and improving institutional access for adaptive farmer groups.